2012
DOI: 10.3851/imp2080
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza a Virus Replication by Antagonism of a PI3K-AKT-mTOR Pathway Member Identified by Gene-Trap Insertional Mutagenesis

Abstract: Background: Host genes serving potential roles in virus replication may be exploited as novel antiviral targets. Methods: Small interfering RNA (siRNA)-mediated knockdown of host gene expression was used to validate candidate genes in screens against six unrelated viruses, most importantly influenza. A mouse model of influenza A virus infection was used to evaluate the efficacy of a candidate FDA-approved drug identified in the screening effort. Results: Several genes in the PI3K-AKT-mTOR pathway were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 42 publications
(42 reference statements)
0
63
1
Order By: Relevance
“…A/Solomon Islands/3/2006 (H1N1) became lethal to mice after seven serial passages in the lungs of infected animals (Murray et al, 2012). To confirm that the mouse-adapted A/Solomon Islands/3/2006 (H1N1) virus was sensitive to amantadine ( 1 ) and compound 3 , plaque assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…A/Solomon Islands/3/2006 (H1N1) became lethal to mice after seven serial passages in the lungs of infected animals (Murray et al, 2012). To confirm that the mouse-adapted A/Solomon Islands/3/2006 (H1N1) virus was sensitive to amantadine ( 1 ) and compound 3 , plaque assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…The results with mTOR inhibitors remain ambiguous. Everolimus therapy improved the outcome with a delay of 1.8 days in death and a marginal survival benefit beyond 14 days post-infection in an animal model 20 . There has been a reported success in human H1N1 virus infection with adjuvant Rapamycin in addition to standard Oseltamivir treatment 21 .…”
Section: Introductionmentioning
confidence: 93%
“…In particular, Akt signaling is involved in influenza virus uptake as well as at the later stages of the virus replication cycle (11)(12)(13)(14). Here, we tested MK2206, an Akt inhibitor, against different influenza virus infections and showed that MK2206 has anti-pH1N1 activity in vitro.…”
mentioning
confidence: 99%